Bidirectional Brush Seals – Post-Test Analysis - Robert C. Hendricks; Jack Wilson; Tom Y. Wu; Ralph Flower; Robert L. Mullen (International Journal of Rotating Machinery)
A post-test analysis of a set of inside-diameter/outside-diameter (ID/OD) bidirectional brush seals used in three-port wave rotor tests was undertaken to determine brush bristle and configuration wear, pullout, and rotor coating wear. The results suggest that sharp changes in the pressure profiles were not well reflected in bristle tip configuration patterns or wear. Also, positive-to-negative changes in axial pressure gradients appeared to have little effect on the backing plates. Although the brushes had similar porosities, they had very different unpacked arrays. This difference could explain the departure of experimental data from computational fluid dynamics flow predictions for well-packed arrays at higher pressure drops. The rotor wear led to “car track” scars (upper and lower wear bands) with a whipped surface between the bands. Those bands may have resulted from bristle stiffening at the fence and gap plates during alternate portions of the rotor cycle. Within the bristle response range the wear surface reflected the pressure distribution effect on bristle motion. No sacrificial metallurgical data were taken. The bristles did wear, with correspondingly more wear on the ID brush configurations than on the OD configurations; the complexity in constructing the ID brush was a factor.